A Study on the Ant Diversity (Hymenoptera: Formicidae) of Periyar Tiger Reserve in South Western Ghats - Sivadasan, Saranya; Anto, Anu; Joseph, Gigi K; Thomas, Shaju (Indian Forester, 2013)
Ants represent a unique focal group, due to their ability to navigate across all trophic levels, along with their sensitivity to any changes in the environment. The present study aims to determine the species composition of ants across varying vegetation types in Periyar Tiger Reserve of Southern Western Ghats. Thirty one (31) species of ants belonging to 14 genus and 4 subfamilies were collected from different habitats of the reserve. This study emphasizes the dominancy exhibited by the subfamily Formicinae within the ant communities, due to their ability to adapt to different niches. Harpegnathos saltator, a species endemic to Western Ghats and Paratrechina longicornis listed in the IUCN red list were collected from the habitat. Out of the total 31 species collected from the five different habitats of the study area, 24 species of ants were found in the semi-evergreen habitat making it the most species rich habitat.